Efficacy of a Physician Assistant Student-Developed Behavior Change Program at a Local Free Clinic. Issue 1 (March 2017) - Cusumano, Judy; Martin, Carla S.; Butler, Brittany; Bixler, Brian; Shirk, Kelsey
Abstract : Purpose: A quality assurance and quality improvement assessment was conducted to evaluate the efficacy of a behavior change program developed by physician assistant (PA) students at a local free clinic. Methods: Physician assistant students developed and implemented a program using motivational interviewing and healthy lifestyle behavioral counseling at a local free clinic. Twenty-eight patients participated in the program over 5 cohorts. A retrospective chart review was used to collect data. Results: Weight and body mass index (BMI) data were gathered retrospectively from patients' charts corresponding to the 6 months before the program, at the start of the program, at the end of the 12-week program, and at 3 and 6 months after the program. Significant differences were found between the start and end of the program for weight ( P < .001) and BMI scores ( P < .001). The mean weight decreased from 111.98 (standard deviation [SD] = 33.47) to 109.00 kg (SD = 33.93). The weight loss ranged from 0.45 to 9.53 kg, and 75% of participants lost weight. The mean BMI decreased from 41.21 (SD = 10.64) to 40.13 (SD = 10.98). Differences were maintained at 3- and 6-month follow-ups. However, only half the sample's data were available at follow-ups because some patients did not return to the free clinic during that time period. Conclusions: A program facilitated by PA students and designed to help patients make healthy diet and exercise changes can be a valuable resource for free clinics and patients and an excellent clinical opportunity for PA students. To strengthen the program's commitment to maintenance of weight loss, program components of continued follow-up and engagement of patients should be explored and developed.